Calcium hydroxide root canal sealers: Evaluation of pH, calcium ion concentration and conductivity - Bezerra Da Silva, L. A.; Leonardo, M. R. [UNESP]; Da Silva, R. S.; Assed, S.; Guimarães, L. F L (My University, 1997)
The calcium hydroxide ionization of four root canal sealers (Sealapex, CRCS, Sealer 26, and Apexit) was studied by measuring conductivity and pH and by conducting atomic absorption spectrophotometry. Samples 6 mm in diameter and 15 mm long were prepared from these sealers. After setting and 48 h storage in a desiccator, five samples of each material were placed in 50 mL distilled water and analysed after 0,1,2,4, 6 and 24 h and 5, 15 and 30 days. The results showed that Sealapex was the root canal sealer showing the highest pH, ionic calcium and total calcium values (P<0.05) throughout the experimental period, followed by CRCS, Apexit and Sealer 26.
Keywords: Calcium hydroxide; Root canal sealers; Apexit; bismuth; Calcibiotic Root Canal Sealer; calcium; calcium hydroxide; root canal filling material; salicylic acid derivative; sealapex; Sealer 26; zinc oxide; atomic absorption spectrometry; chemistry; comparative study; ion exchange; pH; Bismuth; Calcium; Calcium Hydroxide; Hydrogen-Ion Concentration; Ion Exchange; Root Canal Filling Materials; Salicylates; Spectrophotometry, Atomic; Zinc Oxide